Serum of limb remote ischemic postconditioning inhibits fMLP-triggered activation and reactive oxygen species releasing of rat neutrophils - Gangling Chen; Jiangwei Zhang; Mingyue Sheng; Sanli Zhang; Qi Wu; Lei Liu; Boyang Yu; Junping Kou (Taylor & Francis Group, 2021)
Objectives The study explores the protective role of the peripheral serum of limb remote ischemic postconditioning (LRIP) in reducing the reactive oxygen species (ROS) levels and neutrophil activation, which are responsible for the deleterious reperfusion injury. Methods LRIP was induced in Sprague-Dawley rats by three cycles of 5 min occlusion /5 min reperfusion on the left hind limb. The blood samples were collected before LRIP or 0 and 1 h after LRIP (named SerumSham, SerumLRIP0, SerumLRIP1, respectively). The effects of LRIP serum on ROS level and neutrophils activation were determined. The expression of MyD88-TRAF6-MAPKs and PI3K/AKT pathways in neutrophils were examined. Results When compared with SerumSham, SerumLRIP0 and SerumLRIP1 significantly reduced the ROS released from neutrophils activated by fMLP. Meanwhile, the mRNA expression levels of NADPH oxidase subunit p22phox and multiple ROS-producing related key proteins, such as NADPH oxidase subunit p47phox ser 304, ser 345. MyD88, p-ERK, p-JNK and p-P38 expression of neutrophils were downregulated by SerumLRIP0 and SerumLRIP1. SerumLRIP1 also downregulated p47phox mRNA expression and tumor necrosis factor receptor-associated factor 6 (TRAF6) protein expression. Conclusion LRIP serum protects against ROS level and neutrophils activation involving the MyD88-TRAF6-MAPKs. This finding provides new insight into the understanding of LRIP mechanisms.